Enzymeless Glucose Detection Based on CoO/Graphene Microsphere Hybrids. Issue 6 (24th April 2014) - Ci, Suqin; Mao, Shun; Huang, Taizhong; Wen, Zhenhai; Steeber, Douglas A.; Chen, Junhong; Merkoçi, Arben
Abstract An ultrasonic nebulizer‐based spray method was developed to fabricate microshpere hybrids of crumpled graphene (CG) loading cobalt oxide (CoO). The as‐prepared CoO/CG microsphere hybrids were used for constructing an enzymeless sensor for glucose detection in alkaline solution. The as‐developed enzymeless glucose sensor exhibited rapid response (less than 3 s), high sensitivity (669.78 µA mM−1 cm−2), wide detection range (0.83 µM–8.61 mM), good reproducibility and stability, and low detection limit (0.46 µM) (S/N=3). Moreover, the detection of glucose in human blood serum samples with the as‐developed sensor agreed well with the results obtained from commercial glucose meters.